Study on the needs of the older adults with dementia in care institutions based on a hierarchical interaction model: a case study of an institution in Hangzhou, China - Sun, Hong; Chai, Rui; Huang, Song; Xue, Wen; Wang, Zhenhua; Yu, Xinnan; Zhu, Zijun (Frontiers in Public Health, 2025)
Dementia care is a significant public health challenge, particularly in institutional settings where standardized management often conflicts with individual needs. This research investigates the multifaceted needs of older adults with dementia in a Chinese care institution and the extent to which these needs are met. By constructing a stratified interactive framework for need analysis and employing methods such as field observations, in-depth interviews, and surveys, this study comprehensively assessed the satisfaction levels of residents’ multidimensional needs. The findings indicate that while the physiological and safety needs of the residents were largely met, a significant deficit existed in their needs for love and belonging. Furthermore, the Eastern cultural context, with its emphasis on family and collective identity, also influenced the prioritization of needs among this population. Consequently, this study concludes that there is an urgent need to strengthen family interaction and personalized care and proposes a series of targeted interventions, offering theoretical and practical insights for the advancement of person-centered and precise institutional dementia care.